PERANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN MACRO EXCEL DALAM PENGELOLAAN KEUANGAN SATE LUWES: Design of an Accounting Information System Using Excel Macros for Financial Management of Sate Luwes - Pajaria, Annisa Intan; Ginoga, Lesia Fatma; Syahwani, Asty Khairi Inayah; Ramadhanti, Resti Jayeng; Rosyanti, Novi (Politeknik Negeri Jakarta, 2024)
Micro, Small, and Medium Enterprises (MSMEs) significantly contribute to Indonesia's economic growth but often face financial management challenges. This research aims to assist MSMEs in financial management by designing a sales Accounting Information System using Excel Macros, with Sate Luwes as a case study. The data includes primary data from interviews and questionnaires, and secondary data from financial documents at Sate Luwes. The system development method employed is the waterfall model. The research identifies four types of sales transactions at Sate Luwes: on-site transactions, take-away, online, and aqiqah orders. The system design is conducted in three main stages: system analysis, system design, and system implementation. The designed system fulfills internal control components based on Mulyadi's theoretical approach, effectively focusing on application controls. Evaluation results using PIECES analysis indicate that the system successfully meets the needs and expectations of users at Sate Luwes.